Iatrogenic arteriovenous fistula with a saclike widening: alternative means of successful treatment - Kurzawski, Jacek; Zandecki, Łukasz; Piątek, Karolina; Turek, Łukasz; Piątek, Łukasz; Wawak, Magdalena; Sadowski, Marcin (Medical Studies/Studia Medyczne, 2022)
We present 5 cases of iatrogenic arteriovenous fistulas in the unusual form of a channel with a saclike widening. Three of them were treated surgically, while the other 2 were successfully treated with compression of the inflow channel by percutaneous application of tissue glue into the region of the inflow channel and consequent stopping of the blood flow in the arteriovenous fistulas structure. Additional tissue glue application was performed to achieve arteriovenous fistulas sac embolization. This is the first time that such a complication has been treated with a nonsurgical method.